Antiviral immune responses in Itk-deficient mice. - Bachmann, M F (1997)
Mice lacking Itk, a T-cell-specific protein tyrosine kinase, have reduced numbers of T cells and reduced responses to allogeneic major histocompatibility molecules. This study analyzed antiviral immune responses in mice deficient for Itk. Primary cytotoxic T-lymphocyte (CTL) responses were analyzed after infection with lymphocytic choriomeningitis virus (LCMV), vaccinia virus (VV), and vesicular stomatitis virus (VSV). Ex vivo CTL activity was consistently reduced by a factor of two to six for the different viruses. CTL responses after restimulation in vitro were similarly reduced unless exogenous cytokines were added. In the presence of interleukin-2 or concanavalin A supernatant, Itk-deficient and control mice responded similarly. Interestingly, while LCMV was completely eliminated by day 8 in both Itk-deficient and control mice, VV cleared from itk-/- mice with delayed kinetics. Antibody responses were evaluated after VSV infection. Both the T-cell-independent neutralizing immunoglobulin M (IgM) and the T-cell-dependent IgG responses were similar in Itk-deficient and control mice. Taken together, the results show that CTL responses are reduced in the absence of Itk whereas antiviral B-cell responses are not affected.